Palladium-Catalyzed [3+2] Cycloaddition of Vinylcyclopropane and Ketones - Ding, Wen-Ping; Du, Juan; Liu, Xiu-Yan; Chen, Di; Ding, Chang-Hua; Deng, Qing-Hai; Hou, Xue-Long (Synlett, 2019)
A Pd-catalyzed [3+2] cycloaddition reaction of vinylcyclopropane and trifluoromethyl ketones as well as α-keto esters were developed, affording tetrahydrofurans in high yield.
Keywords: palladium; [3+2] cycloaddition; vinylcyclopropane; trifluoromethyl ketone; α-keto ester; tetrahydrofuran